Enhancing Crime Rate Prediction Using Machine Learning Techniques - Bhaludra R Nadh Singh (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Crime is one of the biggest and dominating problem in our society. Daily there are huge number of crimes committed frequently. Here the dataset consists of the date and the crime rate that has taken place in the corresponding years. In this project the crime rate is only based on the robbery. We use linear regression algorithm to predict the percentage of the crime rate in the future by using the previous data information. The date is given as an input to the algorithm and the output is the percentage of the crime rate in that particular year.
Keywords: Crime Rate; Number of Crimes; Regression Algorithm; Machine Learning